2022
DOI: 10.3390/molecules27030663
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Anti-Virulent Activity of Origanum majorana L. Essential Oil on Candida albicans and In Vivo Toxicity in the Galleria mellonella Larval Model

Abstract: The aim of this study was to investigate and compare in detail both the antifungal activity in vitro (with planktonic and biofilm-forming cells) and the essential oil composition (EOs) of naturally growing (OMN) and cultivated (OMC) samples of Origanum majorana L. (marjoram). The essential oil composition was analyzed using GC-MS. The major constituent of both EOs was carvacrol: 75.3% and 84%, respectively. Both essential oils showed high antifungal activity against clinically relevant Candida spp. with IC50 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 68 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…EOs which were able to inhibit mycelial growth of P. commune strain KMi–183 with a very good inhibitory effect (over 80%) at 25 ± 1 °C included only cumin (87.46%) and marjoram (81.71%). In addition, other authors confirmed the good, but not better, antifungal activity of cumin EO against fungal species of Aspergillus flavus [ 31 , 32 ] and some fungal species of the genus Penicillium [ 33 ], and antifungal activity of marjoram EO against Candida albicans [ 34 ]. Eucalyptus and bergamot mint EOs showed the lowest inhibitory effect.…”
Section: Resultsmentioning
confidence: 99%
“…EOs which were able to inhibit mycelial growth of P. commune strain KMi–183 with a very good inhibitory effect (over 80%) at 25 ± 1 °C included only cumin (87.46%) and marjoram (81.71%). In addition, other authors confirmed the good, but not better, antifungal activity of cumin EO against fungal species of Aspergillus flavus [ 31 , 32 ] and some fungal species of the genus Penicillium [ 33 ], and antifungal activity of marjoram EO against Candida albicans [ 34 ]. Eucalyptus and bergamot mint EOs showed the lowest inhibitory effect.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the immune responses of G. mellonella show similarity with the innate vertebrate immune response; thus, these larvae represent an interesting animal model that can be used to prove the virulence of fungal pathogens and the antifungal activity of new compounds [ 39 , 40 , 41 , 42 ]. To investigate the role of compound 12 in terms of the Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, carvacrol prevented biofilm formation, degraded mature C. albicans biofilm, and suppressed various virulence factors of this fungus. Accordingly, carvacrol has the potential to inhibit C. albicans pathogenesis and could be considered in patients with the risk of C. albicans infection or in the with common antifungals was without sufficient success ( Kaskatepe et al, 2022 ). However, for this purpose, further in vivo and clinical studies are needed to evaluate the carvacrol efficiency in clinical setting and further enhance its activity against Candida biofilm.…”
Section: Carvacrolmentioning
confidence: 99%